The culture of Catfish in Nigeria: Progress, prospects and problems - I. K, Chika; Oboroh, Nathaniel (Advances in Aquaculture and Fisheries Management, 2014)
A review of the culture of catfish of the family Claridae in Nigeria was carried out using secondary data. The story of aquaculture in Nigeria is essentially the story of catfish culture. The favoured catfish species include: Clarias gariepinus, Heterobranchus bidorsalis, Clarias × Heterobranchus hybrid (‘Heteroclarias’) and Clarias nigrodigitatus. C. gariepinus and Heterobranchus are the most farmed fish in Nigeria. Catfish farming has continued to attract private sector initiative compared to earlier public or government-sponsored programmes. If the associated problems of production, especially the twin issue of feed production and fingerling supply are tackled, Nigeria will soon become a world exporter of catfish.